The incidence and distribution of stress fractures in elite tennis players - Maquirriain, J.; Ghisi, J. P. (British Journal of Sports Medicine, 2006)
Background: Modern professional tennis involves powerful movements repeatedly subjecting the musculoskeletal system to heavy mechanical load. Thus tennis players are exposed to high risk of overuse injuries including stress fractures.